Analysis of the Canadian Mining Industry’s Global Engagement Practices with Indigenous Peoples - Ardakani, Azadeh (2011)
The aim of this research is to give a summary of how mining companies address issues of Indigenous communities from a cultural and human rights perspective. In the last 10 to 15 years, coinciding with globalization (Murphy & Arenas, 2011), increased market demands, as a result of population and economic growth, resource extraction industries have been shifting their operations from developed to developing countries (Mining Journal, November 2001, p. 353). (Murphy & Arenas, 2011). As a result, Indigenous Peoples have suffered from development on their traditional lands, specifically from the implications of development on their cultures, economies and societies. There have been growing ethical concerns about the mining industry. Environmental and human rights disasters related to the mining sector have become high profile ethical issues in many countries and contributed to growing public and media concern. The “Management In Mining Report” has cited bribery, lack of community engagement, harmful affects on agricultural land, pollution and related health hazards, as reasons for criticism. Can Corporate Social Responsibility (CSR) cause a fundamental change in protecting the rights of these vulnerable communities, and contribute to a fair distribution of costs and benefits from this large-scale resource exploitation? If so, under what conditions can this occur? This research thesis aims to determine the enablers and barriers in this process for the sake of Indigenous empowerment, as opposed to management, based on a renewed understanding of the mechanisms at play. Furthermore, the literature review will look at the role of the state in community rights and corporate responsibility, corporate attempts to justify and regulate community efforts in local development, and the ways by which civil society and NGOs can work to ensure the social and ecological sustainability of mineral extraction.